STABILITY AND ACTIVITY OF LIPID A PHOSPHOETHANOLAMINE TRANSFERASE FROM NEISSERIA MENINGITIDIS IN THE PRESENCE OF SODIUM DEOXYCHOLATE [STABILITAS DAN AKTIVITAS LIPID A PHOSPHOETHANOLAMINE TRANSFERASE DARI NEISSERIA MENINGITIDIS TERHADAP PENAMBAHAN NATRIUM DEOKSIKOLAT] - Samantha, Ariela; Sihombing, Caitlyn Christvania; Vrielink, Alice (Universitas Pelita Harapan, 2024)
Antibiotics are often used to fight infections caused by pathogenic bacteria. However, inappropriate use of antibiotics has caused many pathogenic bacteria to gain antibiotic resistance. Some resistance mechanisms arise through enzymatic modification of the bacterial membrane. Lipid A phosphoethanolamine transferase (EptA) modifies bacterial membranes through the addition of phosphoethanolamine to the lipid A moiety of lipopolysaccharide (LPS) or lipooligosaccharide (LOS). Inhibition of EptA would therefore restore the antibiotic susceptibility of the bacterium. In order to develop inhibitors against EptA, in vitro studies are required. Biochemical studies of membrane proteins such as EptA, must be carried out in buffers containing detergent to ensure the solubility and stability of the membrane protein. EptA has been found to be most stable in buffers containing the detergent, n-dodecyl Î²-D-maltoside (DDM). However, due to the fact that LOS is also required for biochemical studies of EptA, the detergent, sodium deoxycholate (DOC) is also required as it prevents the aggregation of LOS. In this study, the stability and activity of EptA in the presence of DOC were investigated using thin layer chromatography (TLC) and circular dichroism (CD) spectroscopy. Additionally, preliminary studies on the interaction of EptA and LOS in vitro was carried out using native agarose gel electrophoresis (NAGE). This study shows that EptA remains active in the presence of ‰¤ 2 mM DOC with the highest activity observed in buffers containing only 1 mM DOC. CD analysis showed that the overall secondary structure of EptA in buffer containing various concentrations of DDM and DOC was maintained. Additionally, through NAGE analysis the interaction between EptA and LOS was successfully observed. Therefore, further in vitro studies incorporating both substrates with supplementation of up to 1 mM DOC could be carried out with the long-term goal of studying inhibitors against EptA.Bahasa Indonesia Abstract:Antibiotik sering digunakan untuk melawan infeksi yang disebabkan oleh bakteri patogen. Namun, penggunaan antibiotik yang tidak tepat telah menyebabkan banyak bakteri patogen mendapatkan resistensi antibiotik. Beberapa mekanisme resistensi muncul melalui modifikasi enzimatik dari membran bakteri. Lipid A phosphoethanolamine transferase (EptA) mengubah membran bakteri dengan menambahkan fosfoetanolamina ke bagian lipid A dari lipopolisakarida (LPS) atau lipooligosakarida (LOS). Penghambatan EptA akan mengembalikan kerentanan antibiotik dari bakteri tersebut. Untuk mengembangkan inhibitor terhadap EptA, studi in vitro diperlukan. Studi biokimia protein membran seperti EptA, harus dilakukan dalam larutan penyangga yang mengandung deterjen untuk memastikan kelarutan dan stabilitas protein membran. EptA ditemukan paling stabil dalam larutan penyangga yang mengandung deterjen, n-dodecyl Î²-D-maltosida (DDM). Namun, karena LOS juga diperlukan untuk studi biokimia EptA, deterjen, sodium deoksikolat (DOC) juga diperlukan karena mencegah agregasi LOS. Dalam penelitian ini, stabilitas dan aktivitas EptA dalam keberadaan DOC diselidiki menggunakan kromatografi lapis tipis (TLC) dan spektroskopi dikroisme sirkular (CD). Selain itu, studi awal tentang interaksi EptA dan LOS in vitro dilakukan menggunakan elektroforesis gel agarosa asli (NAGE). Studi ini menunjukkan bahwa EptA tetap aktif dalam keberadaan ‰¤ 2 mM DOC dengan aktivitas tertinggi diamati dalam larutan penyangga yang hanya mengandung 1 mM DOC. Analisis CD menunjukkan bahwa struktur sekunder keseluruhan EptA dalam larutan penyangga yang mengandung berbagai konsentrasi DDM dan DOC tetap terjaga. Selain itu, melalui analisis NAGE, interaksi antara EptA dan LOS berhasil diamati. Oleh karena itu, studi in vitro lebih lanjut yang memasukkan kedua substrat dengan suplementasi hingga 1 mM DOC bisa dilakukan dengan tujuan jangka panjang untuk mempelajari inhibitor terhadap EptA.